Using instructor judgment, learner corpora, and DIF to develop a placement test for Spanish L2 and heritage learners. (July 2022) - Bowles, Melissa A.
This study details the development of a local test designed to place university Spanish students ( n = 719) into one of the four different course levels and to distinguish between traditional L2 learners and early bilinguals on the basis of their linguistic knowledge, regardless of the variety of Spanish they were exposed to. Early bilinguals include two groups—heritage learners (HLs), who were exposed to Spanish in their homes and communities growing up, and early L2 learners with extensive Spanish exposure, often through dual immersion education, who are increasingly enrolling in university Spanish courses and tend to pattern with HLs. Expert instructor judgment and learner corpora contributed to item development, and 12 of 15 written multiple-choice test items targeting early-acquired vocabulary had differential item functioning (DIF) according to the Mantel–Haenszel procedure, favoring HLs. Recursive partitioning revealed that vocabulary score correctly identified 597/603 (99%) of L2 learners as such, and the six HLs whose vocabulary scores incorrectly identified them as L2 learners were in the lowest placement groups. Vocabulary scores also correctly identified 100% of the early L2 learners in the sample ( n = 7) as having a heritage profile. Implications for the local context and for placement testing in general are provided.